A Shadow of Glory Reading the New Testament After the Holocaust. - Linafelt, Tod. (Hoboken : Taylor and Francis, 2013)
First Published in 2003.
Description based upon print version of record.
Keywords: Bible. New Testament -- Criticism, interpretation, etc; Holocaust (Christian theology).; Bible. -- Criticism, interpretation, etc; Holocaust (Christian theology); RELIGION / Biblical Studies / New Testament; Electronic books